2001
DOI: 10.1016/s0921-4488(01)00196-1
|View full text |Cite
|
Sign up to set email alerts
|

Light microscopical and ultrastructural characterization of goat preantral follicles

Abstract: Light microscopical and ultrastructural characterization of goat preantral follicles AbstractGoat ovarian preantral follicles were morphologically and ultrastructurally described in this work. Primordial follicles are oocytes surrounded by one layer of squamous or squamouscuboidal granulosa cells; primary follicles have a single layer of cuboidal granulosa cells, and secondary follicles are oocytes surrounded by two or more layers of cuboidal granulosa cells. At all developmental stages a thick layer of glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
53
3
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 41 publications
14
53
3
3
Order By: Relevance
“…primordial, primary and secondary). Also, our results were similar to those described for humans [39], but different from those described for ewes [40] and goats [41]. In addition, some polyovular follicles could be observed in Zebu cow ovaries.…”
Section: Discussionsupporting
confidence: 65%
“…primordial, primary and secondary). Also, our results were similar to those described for humans [39], but different from those described for ewes [40] and goats [41]. In addition, some polyovular follicles could be observed in Zebu cow ovaries.…”
Section: Discussionsupporting
confidence: 65%
“…The results showed that the mean diameter of zebu oocytes and follicles and the mean number of granulosa cells at the equatorial section were similar to those observed for European cattle (Van Wezel and Rodgers, 1996, Braw-Tal and Yossefi, 1997and Hyttel et al, 1997 in all three developmental stages evaluated (i.e., primordial, primary and small secondary follicles). Also, our results were similar to those described for humans (Lintern-Moore et al, 1974), but different from those described for ewes (Lundy et al, 1999) and goats (Lucci et al, 2001). …”
Section: Discussionsupporting
confidence: 65%
“…The most important difference observed concerned the mitochondria. Round mitochondria are commonly found in oocytes, and were described in European cattle ( Fair et al, 1997a andHyttel et al, 1997) and goats ( Lucci et al, 2001), especially in primordial and primary follicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primordial follicles are quiescent, whereas primary follicles are already activated and in early growth. Although the mechanisms of primordial follicle activation are yet undefined, it is well known that oocyte and granulosa cells from primary follicles undergo fast and substantial transformations, such as granulosa cell proliferation and change in shape, oocyte growth and proliferation of cytoplasmic organelles in both cell types [22], [23] and [24]. Cells undergoing such transformations may be more sensitive to environmental factors, and thus degenerate under conditions of reduced temperature.…”
Section: Discussionmentioning
confidence: 99%